Bioactivity of an Ionic Liquid against Two Major Coleopteran Stored Grain Insect Pests - Brari, Jyotika (International Journal of Pharmaceutical & Biological Archive, 2021)
Introduction: Insecticidal efficacy of a monoterpene-based ionic liquid was evaluated against two Coleopteran insect pests, viz., the red flour beetle, Tribolium castaneum Herbst. and the drug store beetle, Stegobium paniceum (L). Methods: Bioassays for contact activity against adult insects, larvicidal activity, repellent activity, and antifeedant activity were conducted in the laboratory for the above said insect pests. Results: Ionic liquid at a highest concentration of 1.0 μl/cm2 proved to be most effective against adults of S. paniceum producing 76.23 ± 1.9% mortality while 70.12±3.5% mortality was obtained against T. castaneum after 72 h, respectively. T. castaneum larvae were most susceptible to all the doses of ionic liquid at a highest dose of 100 μl/ml of ionic liquid 80.08 ± 2.2 mortality was obtained followed by a mortality of 68.32±1.8% for S. paniceum among 8-10 day old larvae. Ionic liquid showed remarkable repellency at different doses of 2, 6 and 10 μl/cm2 against both insect pests. For S. paniceum 75.45 ± 1.9, 80.28 ± 2.4 and 56.35 ± 4.8% repellency was observed at 10 μl/cm2 of ionic liquid after 3, 5 and 24 h. Ionic liquid proved to be effective seed protectant against both the insect pests. 87.99 ± 0.14% FDI was recorded with 5.10 ± 0.30 grain damage at 300 μl/g of ionic liquid, respectively, while 72.32 ± 0.18% grain damage was observed in control for T. castaneum.